Identidade profissional e precarização do trabalho: uma avaliação em profundidade da política municipal de fiscalização urbana de Fortaleza, Ceará - Lima, Rachel Figueiredo Viana Martins (2022)
This dissertation aims to evaluate the municipal inspection policy of Fortaleza, established by Complementary Law nº 190, of December 22, 2014, focusing on the issues that articulate the precariousness of work and professional identity. To this end, the research field is the Fortaleza Inspection Agency (AGEFIS), due to the institutionalization of a municipal policy of integrated inspection that, centered on neoliberal logic since the 1970s, has been putting on the scene several transformations in professional ties. of inspectors with their category and with the meanings given to the work. The research is based on the in-depth evaluation approach (RODRIGUES, 2008, 2011a and 2016), as the focus is to carry out an analysis in multiple dimensions of the program and, in this sense, to apprehend the subjectivities of the various actors involved in the policy. The idea is to carry out an evaluation that allows the confluence of paradigms, putting in dialogue, above all, the interpretivist with the critic. From the methodological point of view, the research has a qualitative nature with emphasis on the analysis of official documents, bibliographic research, field observations and semi-structured interviews. The research also aims to point out the construction of evaluation indicators from the qualitative data collected, bringing contributions to the evaluation of the municipal inspection policy in Fortaleza. Among the results obtained in the field research, it is revealed that the precariousness of AGEFIS inspectors is linked to the generalization of their competences, the standardization of inspection actions and the search for the productivity goal that lead to the loss of quality of inspection work and end up for generating insecurity, instability, illness among the servers and lack of identification with the work they perform.